臺北市銘傳國小學童使用學校圖書館影響因素研究 Influential Factors of the Students’ Usage in the Taipei Municipal Mingchuan Elementary School Library: A field study - Kun-Yu Lai; Shan-Ju L. Chang (Jiàoyù zīliào yǔ túshūguǎn xué, 2010)
本研究採質性研究方法,透過半結構式深度訪談、參與觀察、館員日誌及圖文徵集資料解析等方法,以臺北市銘傳國小學童為研究對象,訪談16位中、高年級學童;有目的性地觀察記錄學童在館內活動情形,並輔以簡短非正式訪談,以瞭解學童在學校圖書館內之使用情形,歸納解析學童使用學校圖書館之影響因素為圖書館因素及非圖書館因素。 本研究歷經四個月的深度訪談及十四個月的觀察記錄,研究發現影響學童使用學校圖書館的因素可歸納為館藏、館舍與設備,以及館員、閱讀推廣活動與館規等三個面向。非圖書館因素包括課業與補習、重要他人及校內活動等因素。同時,本研究更發現:一個以館藏為核心、以學童為主體、無安靜壓力、歡迎學童、溫馨似家的閱讀環境,正是學童樂於前往使用的重要因素。因為親切,所以喜悅;因為舒適,所以享受;因為明亮,所以安全;因為隨時開放,所以方便取用;因為溫馨,所以有一種想留下來看書的感覺。學童在其間所發生的社會性互動,透過共讀、討論與分享所流露之歡愉,正是其人際關係的學習和知識分享的實踐。 根據研究結論,研究者對家長、館員、學校及教育當局提供若干建議,期以現況之探索研究,做為提升銘傳國小圖書館服務品質之參考,並探索未來小學圖書館發展的可能樣貌。 In the past twenty years, most studies of elementary school libraries were about how the library was used. However, little research regarding why students would like to visit the library and what are their favorites in the library has been carried out. The purpose of this study is thus to understand the influential factors of graders library use at school library. This study adopted the qualitative research in a semi-structured in-depth interview and a participant observation research. The interviewed objects are sixteen 3~6 graders who borrowed books or media frequently from the school library. There are some influential factors can affect the library use including library factor and non-library factors such as: the abundance and attractiveness of collections; the independence and distance of premises, the comforts of interior space; the equipments including network, light, air-conditioner, and audio-video facilities; the competence and friendly support of the librarian, the reading activities, and longer opening hour. Moreover, the schoolwork, the significant persons and the others, etc. are also important. The analyses found that the function of the school library lies not only on reading, circulating and searching, but also being a place for leisure and social activities. That is a successful school library which is not only a library, but also a living room at home. Ideally, the school should enhance the positive linkage between the students and the library as well as the librarian should be a facilitator to connect them. On the other hand, the librarian should encourage students read enthusiastically by making library as a warm, convenient, and comfortable environment. As a result, the student would like to be a long-term patron of the library.